How Jewish Values and The Chavruta, Student Learning Groups, Support Cooperative Learning - Solomon, Richard D.; Greene, Wallace; Davidson, Neil (Autonómia és Felelősség Neveléstudományi Folyóirat, 2024)
While cooperation in education may seem to be a twentieth-century development, it has long-standing origins in many societies. For example, an ancient Jewish tradition of having a learning partner (Chavruta) with whom to study the Talmud is referenced as early as the Babylonian Talmud (Shabbat 63a). Cooperative learning (CL) has developed in secular education over a period of more than fifty years. Eventually, some of us realized that the core values of cooperative learning are compatible with the values of the world's religions. In this paper we examine the relationship between cooperative learning and selected values within Judaism.